Understanding the importance of attachment in the experiences of shame of people living with HIV: The role of emotion regulation processes - Arsénio, Paulo Francisco Craveiro (2022)
Dissertação de Mestrado em Intervenções Cognitivo-Comportamentais em Psicologia Clínica e da Saúde apresentada à Faculdade de Psicologia e de Ciências da Educação